UNDERSTANDING PERSONALITY - harni jusuf (LP2M IAIN Sultan Amai Gorontalo, 2018)
Educational can not be separeted from learning. To support the successful of teaching learning process, it must be supported by some apsects, such as: learning syles, teaching strategies, affective factors, and socio-cultural factors. One of the affective factors that must be pay attention in language learning is personality. Personality is a term in psychology which is depict the character of a person in everyday life. As human beings experience growth and development, personality also experiences development and change. That is why personality can be measured. One way to measure personality is by using psychometric.